Системи підготування повітря для ручних машин - Баранов, Ю. О.; Косминський, І. В.; Мельниченко, М. С. (Техніка будівництва, 2020)
In detail the system for manual preparation of air vehicles. Made detailed recommendations on the selection of pneumatic systems on construction for pneumatic hand tools. Found 35, 2015 43 that olohoviddilnyky recommended in conjunction with line filters, and moisture separators installed after the filter. It provides the most effective treatment: filter retains solids, oil and much of the water and the remaining water will be delayed watersplitted. It was found that after complete cleaning of the air condensate falls back upon further fall in temperature. It is proposed to establish volohovvidilyuvach in the place the highway, where the temperature is a minimum value